Analisis Kualitas Abon Berbahan Dasar Carica - Yatno, Hendi Wiji; Nugroho, Setyo Prasiyono; Istiraharsi, Yedna; Karmin, Enny (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Ampat Yogyakarta, 2023)
Abon is a type of processed food that has a long storage time. Abon meat is usually processed from shredded animal meat which is then seasoned with spices and fried and then drained until it is completely dry. Abon can be created by changing the raw materials into other raw materials with similar textures. Other raw materials can be in the form of vegetables or fruits depending on needs. Abon made from carica fruit is a new innovation to increase the nutritional quality of shredded and the selling value of carica fruit, which is often found in the Wonosobo area. This research is an experimental type that aims to find out how the quality of carica-based shredded meat is seen from the aspect of aroma, taste, color, texture and appearance which was tested on 2 experts and 30 panelists chosen by researchers with various considerations. The analytical method used by the researcher is descriptive statistics which is done by tabulating the results of the questionnaire in the form of a single table. The table in question can provide a general description of the panelists' responses to the quality of shredded carica based on the tendency of the rating results, then interpretation is carried out to understand the meaning behind this tendency. Based on the results of the research and the results of panelist interviews on the quality of abon carica on the aspects of aroma, taste, color, and texture, the average value of 5 or which means